Incidental thyroid nodule. (4th March 2009) - Patel, Chirag N; Gerrard, Georgina; Scarsbrook, Andrew F
Abstract : Thyroid nodules may be coincidentally detected as a result of neck imaging, and most are benign; the authors discuss how best to decide which nodules are most likely to be malignant and require further evaluation